99mTc-Sestamibi/123I Subtraction SPECT/CT in Parathyroid Scintigraphy: Is Additional Pinhole Imaging Useful?. (18th October 2017) - Tunninen, Virpi; Varjo, Pekka; Kauppinen, Tomi; Holm, Anu; Eskola, Hannu; Seppänen, Marko
Abstract : Objectives . This retrospective study evaluated whether the use of additional anteriorT c 99 m -sestamibi/ 123 I pinhole imaging improves the outcome ofT c 99 m -sestamibi/ 123 I subtraction SPECT/CT in parathyroid scintigraphy (PS). Materials and Methods . PS using simultaneous dual-isotope subtraction methods and an acquisition protocol combining SPECT/CT and planar pinhole imaging was performed for 175 patients with primary or secondary hyperparathyroidism. All patients who proceeded to surgery with complete postsurgery laboratory findings were included in this study( n = 94 ) . SPECT/CT images alone and combined with pinhole images were evaluated. Results . There were 111 enlarged parathyroid glands of which 104 and 108 glands were correctly visualized by SPECT/CT (seven false positives) or SPECT/CT with pinhole (three false positives), respectively. Both sensitivity and specificity were higher with combined SPECT/CT with pinhole than with SPECT/CT alone (97% versus 94% and 99% versus 98%, resp., not significant). The false-positive rate was 6% with SPECT/CT and decreased to 3% using combined SPECT/CT with pinhole. Conclusion .T c 99 m -sestamibi/ 123 I subtraction SPECT/CT is a highly sensitive and specific protocol for PS. The use of additional anterior pinhole imaging increases both sensitivity and specificity of PS, although this increase is not statistically significant.